Penerapan Metode Drill and Practice untuk Meningkatkan Pemahaman Guru Akuntansi SMK dalam Penyusunan Laporan Arus Kas - Vita Fitria Sari; Mayar Afriyenti (Universitas Negeri Padang, 2021)
The objective of this research is determine whether there is difference in the teacher's understanding of the material for preparing cash flow reports before and after receiving training treatment for preparing cash flow reports by applying the drill and practice method. This research categorized as pre-experimental (nondesign) by the method of the one group pretest – posttest design. Data analysis carried out using independent sample t-test. The results indicated that there is difference in the understanding of accounting teachers on the material for preparing cash flow statements before and after receiving treatment in the form of training in preparing cash flow reports by applying the drill and practice method. The application of drill and practice method can be recommended as an alternative learning method for accounting.